ANALISIS PERBANDINGAN KURIKULUM PENDIDIKAN KOREA SELATAN DAN INDONESIA - Evy Marita Yuliwinarti; Hitta Alfi Muhimmah; Nurul Istiqfaroh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to analyze and find out in more depth regarding the comparison between the South Korean and Indonesian education curricula. The type of research used in this research is literature study. The data source in this research comes from journals or scientific articles. The journals in this research were obtained via Google Scholar with a total of 11 journals obtained. The research results show that there are differences between the two countries, namely in their educational curriculum. The South Korean education curriculum focuses on providing competency provisions to students so they are ready to enter the world of work. Meanwhile, the Indonesian curriculum focuses on responding to the challenges of the 4.0 revolution era. Therefore, Indonesia needs to take several examples from the South Korean education curriculum, especially in preparing provisions so that students are ready to enter the world of work considering that in this country there are still many unresolved unemployment problems.